2021
DOI: 10.1007/s00420-021-01660-8
|View full text |Cite
|
Sign up to set email alerts
|

Vibration related symptoms and signs in quarry and foundry workers

Abstract: Purpose The development of vascular and neurosensory findings were studied in two groups of long-term exposed quarry and foundry workers with different vibration exposures, working conditions and work tasks. Methods The study included 10 quarry workers (mean age 43 yrs., mean exposure time 16 yrs.) and 15 foundry workers (35 yrs.; 11 yrs.) at two plants in Sweden. All participants completed a basic questionnaire and passed a medical examination including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“… 8 - 11 The health implications are diverse, encompassing hearing challenges, accidents resulting from machine operations, and injuries caused by stones and gravels during the processing phase. Compounding these issues, Gerhardsson et al 12 highlighted the development of heart problems among workers due to vibrations from the machinery. The heavy vibrations generated by these machines have also been reported to affect the structural integrity of residential buildings in the vicinity, leading to the displacement of original dwellers, predominantly farmers.…”
Section: Introductionmentioning
confidence: 99%
“… 8 - 11 The health implications are diverse, encompassing hearing challenges, accidents resulting from machine operations, and injuries caused by stones and gravels during the processing phase. Compounding these issues, Gerhardsson et al 12 highlighted the development of heart problems among workers due to vibrations from the machinery. The heavy vibrations generated by these machines have also been reported to affect the structural integrity of residential buildings in the vicinity, leading to the displacement of original dwellers, predominantly farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the industrial sector have found neurological and vascular disorders due to use of power tools (Figure 2), where blood vessels are damaged (Cederlund et al, 2001; Gerhardsson et al, 2021) Due to Hand‐arm Vibration (HAV), muscles and tissues of the hand are poorly affected, which increases the chances of disabilities during work (Barr & Barbe, 2004; Winkelstein, 2004). In a motorcycle chassis production firm, it was found that injuries and accident rates are high due to the loss of sensation of the hands (Forouharmajd et al, 2017).…”
Section: Introductionmentioning
confidence: 99%